Formaldehyde-free flame-retardant adhesive, preparation method thereof and application of formaldehyde-free flame-retardant adhesive in artificial board
By using legacy-free flame-retardant adhesives prepared with non-toxic polyethyleneimine and phytic acid materials, the formaldehyde emission and flammability problems of traditional adhesives in artificial boards are solved, and the green and environmentally friendly production and excellent flame-retardant performance of artificial boards are achieved.
Patent Information
- Application Number
- CN202410945077.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional artificial board adhesives have formaldehyde release problems during use, which endangers human health. Moreover, artificial boards are flammable, causing rapid combustion during fires, causing casualties and property losses.
The aldehyde-free, non-toxic polyethyleneimine (PEI) and phytic acid are used as raw materials, and the cross-linking modification of cross-linking agents is synergistically used to prepare a flame-retardant adhesive without precipitation. The adhesive does not involve toxic chemicals during the preparation process, and the process is simple and convenient for industrial production.
This adhesive not only gives artificial board good mechanical properties, but also has excellent flame retardant effect, which improves the added value of artificial board, replaces traditional "trialdehyde" adhesive, solves the problems of formaldehyde pollution and flammability, and realizes a green and environmentally friendly production process.
Smart Images

Figure CN119570436A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives for artificial boards, and in particular relates to an aldehyde-free flame-retardant adhesive, a preparation method thereof, and application in artificial boards. Background Art
[0002] Artificial boards are made of wood or other non-wood plants as raw materials, separated into various unit materials through certain mechanical processing, and then glued together with or without adhesives and other additives. They mainly include three categories of products: plywood, particle (chip) board and fiberboard, which are widely used in furniture manufacturing, building decoration, packaging boxes, flooring, wall panels and other fields.
[0003] In order to give artificial boards good mechanical properties, adhesives are indispensable. At present, adhesives for artificial boards mainly include three categories: urea-formaldehyde resin adhesives, modified melamine adhesives and phenolic resin adhesives. Although these adhesives can give artificial boards good properties, there is a problem of formaldehyde release during the production and use process, which endangers people's health and seriously affects people's pursuit of a beautiful and green home life. In addition, the main raw material of artificial boards is wood material, which is easy to burn. Once a fire occurs, the burning speed is extremely fast, which can easily cause casualties and property losses.
[0004] Therefore, the development of a formaldehyde-free and flame-retardant adhesive for artificial boards has important practical significance. It can not only realize the formaldehyde-free and green nature of artificial boards, but also give artificial boards good flame retardant properties, increase their added value and application areas, and help promote the green, efficient and sustainable development of the artificial board industry. Summary of the invention
[0005] The present invention provides a formaldehyde-free flame-retardant adhesive, a preparation method thereof and application in artificial boards, aiming to solve the formaldehyde pollution problem caused by the use of traditional "trialdehyde" and the problem that the artificial boards themselves are not flame-retardant.
[0006] The present invention is achieved by a method for preparing a formaldehyde-free flame-retardant adhesive, comprising the following steps:
[0007] S1: Weigh a certain amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH value, and prepare a PEI aqueous solution;
[0008] S2: Weigh a certain amount of phytic acid stock solution, dissolve it in water, and stir evenly to prepare a phytic acid aqueous solution;
[0009] S3: Mix the PEI aqueous solution and the phytic acid aqueous solution according to a certain ratio, and slowly stir for several hours to obtain a brown viscous substance which is deposited at the bottom of the cup, thereby obtaining a PEI-phytic acid polymer adhesive;
[0010] S4: Add a crosslinking agent to the PEI-phytic acid polymer adhesive and stir evenly to obtain a crosslinked PEI-phytic acid polymer adhesive.
[0011] Preferably, in step S1, the pH is 9-10, the concentration of the prepared PEI aqueous solution is 2.5%-10%, and the molecular weight of polyethyleneimine is 7000-100000.
[0012] Preferably, in step S2, the concentration of the prepared phytic acid aqueous solution is 2.5%-10%.
[0013] Preferably, in step S3, the mass ratio of the PEI aqueous solution to the phytic acid aqueous solution is 0.25-4.
[0014] Preferably, in step S4, the cross-linking agent includes boric acid and a metal salt.
[0015] A formaldehyde-free flame-retardant adhesive is prepared by the above-mentioned preparation method.
[0016] Application of the above-mentioned formaldehyde-free flame-retardant adhesive in wood-based panels:
[0017] When preparing wood plywood, apply formaldehyde-free flame retardant adhesive at a single-sided application rate of 80-150g / m 2 Apply it to the plate, and then bond it to another plate, and hot press it for 5-15 minutes at a hot pressing temperature of 120-220℃ and a hot pressing pressure of 1-3MPa.
[0018] When preparing fiberboard or particleboard, the formaldehyde-free flame-retardant adhesive is sprayed onto the surface of the fiber or particle board, and hot pressing is performed for 5-15 minutes at a hot pressing temperature of 160-220° C. and a hot pressing pressure of 1-3 MPa.
[0019] Beneficial Effects
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses formaldehyde-free, non-toxic PEI and phytic acid as raw materials, and prepares a formaldehyde-free adhesive by precise control of the ratio and multiple bonding between PEI and phytic acid, and synergistic cross-linking modification of the cross-linking agent, which can not only give the artificial board good mechanical properties, but also make the artificial board have excellent flame retardant effect, improve its added value, achieve the purpose of "one agent for two uses", and is expected to replace the traditional "trialdehyde" adhesive;
[0021] (2) The raw materials used in the present invention are rich in carbon, nitrogen or phosphorus elements, have good carbon-forming effect and flame retardant effect, and can further improve the flame retardant properties of the artificial board under the synergistic cross-linking effect of boric acid and metal salt;
[0022] (3) The preparation process of the adhesive of the present invention is simple, requiring only simple stirring, and does not require the complex synthesis process of "trialdehyde" glue, so it is easy to realize industrial production; and the preparation process does not involve any toxic or harmful chemicals and solvents. The synthesis process and the prepared artificial board are green and environmentally friendly, and have great commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the molecular structure of the PEI-phytic acid adhesive and its cross-linked adhesive in the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0025] The present invention provides a technical solution: a method for preparing a formaldehyde-free flame-retardant adhesive, comprising the following steps:
[0026] S1: Weigh a certain amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH value, and prepare a PEI aqueous solution.
[0027] The pH of the prepared PEI aqueous solution is 9-10, the concentration is 2.5%-10%, and the molecular weight of polyethyleneimine is 7000-100000. The molecular weight of polyethyleneimine can be 7000, 10000, 70000, 100000, etc.
[0028] The concentration of the PEI aqueous solution may be 2.5%, 5%, 7.5%, 10% or other concentrations.
[0029] S2: Weigh a certain amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution.
[0030] The concentration of the phytic acid stock solution is 50%, and the concentration of the prepared phytic acid aqueous solution is 2.5%-10%, which can be 2.5%, 5%, 7.5%, 10% or other concentrations.
[0031] S3: The PEI aqueous solution and the phytic acid aqueous solution are mixed according to a certain ratio, and the mixture is slowly stirred for several hours to obtain a brown viscous substance which is deposited at the bottom of the cup, thereby obtaining a PEI-phytic acid polymer adhesive.
[0032] The mass ratio of the PEI aqueous solution to the phytic acid aqueous solution is 0.25-4.
[0033] The ratio of the PEI aqueous solution to the phytic acid aqueous solution can be 4:1, 2:1, 1:1, 1:2, or 1:4.
[0034] S4: adding a cross-linking agent to the PEI-phytic acid polymer adhesive and stirring the mixture evenly to obtain a cross-linked PEI-phytic acid polymer adhesive.
[0035] In order to improve the water resistance of the adhesive, the adhesive is further modified by a cross-linking agent, which includes boric acid and metal salts, and the metal salts specifically include calcium salts, iron salts, magnesium salts, zinc salts, copper salts, manganese salts, etc. The amount of boric acid used is 0.5%-2% of the mass of the PEI-phytic acid polymer adhesive.
[0036] The concentration of the metal salt solution is 0.5%-2% of the mass of the PEI-phytic acid adhesive.
[0037] A formaldehyde-free flame-retardant adhesive is prepared by the above-mentioned preparation method.
[0038] Application of the above-mentioned formaldehyde-free flame-retardant adhesive in wood-based panels:
[0039] When preparing wood plywood, apply the formaldehyde-free flame-retardant adhesive on the board with a single-sided application amount of 80-150g / m2, and then bond it to another board and hot press it for 5-15 minutes at a hot pressing temperature of 120-220°C and a hot pressing pressure of 1-3MPa.
[0040] When preparing fiberboard or particleboard, the formaldehyde-free flame-retardant adhesive is sprayed onto the surface of the fiber or particle board, and hot pressing is performed for 5-15 minutes at a hot pressing temperature of 160-220° C. and a hot pressing pressure of 1-3 MPa.
[0041] Embodiment 1:
[0042] Step 1: Weigh an appropriate amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH to 9-10, and prepare a 5% PEI aqueous solution;
[0043] Step 2: Weigh an appropriate amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution with a concentration of 5%;
[0044] Step 3: Mix the PEI aqueous solution and the phytic acid aqueous solution in a ratio of 1:1, and continue to slowly stir for 4 hours to obtain a brown viscous substance that is deposited at the bottom of the cup, which is the desired PEI-phytic acid polymer adhesive.
[0045] Step 4: At a hot pressing temperature of 120°C, a hot pressing pressure of 1.5 MPa, a hot pressing time of 8 minutes, and a single-sided glue amount of 120 g / m 2 Under the condition of , two-layer (6mm thick) gluing specimens were prepared by hot pressing. The present invention prepared wood gluing specimens (overlap area 25mm*25mm) by overlapping, and coated the adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0046] Embodiment 2:
[0047] Step 1: Weigh an appropriate amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH to 9-10, and prepare a 5% PEI aqueous solution;
[0048] Step 2: Weigh an appropriate amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution with a concentration of 5%;
[0049] Step 3: Mix the PEI aqueous solution and the phytic acid aqueous solution in different ratios of 1:2, and continue to slowly stir for 4 hours to obtain a brown viscous substance that is deposited at the bottom of the cup, which is the desired PEI-phytic acid polymer adhesive.
[0050] Step 4: At a hot pressing temperature of 120°C, a hot pressing pressure of 1.5 MPa, a hot pressing time of 8 minutes, and a single-sided glue amount of 120 g / m 2 Under the condition of , a 2-layer (6 mm thick) gluing specimen was prepared by hot pressing. The present invention prepares a wood gluing specimen (overlap area 25 mm*25 mm) by overlapping, and coats the adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0051] Embodiment three:
[0052] Step 1: Weigh an appropriate amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH to 9-10, and prepare a 10% PEI aqueous solution;
[0053] Step 2: Weigh an appropriate amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution with a concentration of 10%;
[0054] Step 3: Mix the PEI aqueous solution and the phytic acid aqueous solution in different ratios of 1:1, and continue to slowly stir for 4 hours to obtain a brown viscous substance that is deposited at the bottom of the cup, which is the desired PEI-phytic acid polymer adhesive.
[0055] Step 4: At a hot pressing temperature of 120°C, a hot pressing pressure of 1.5 MPa, a hot pressing time of 8 minutes, and a single-sided glue amount of 120 g / m 2 Under the condition of , a 2-layer (6 mm thick) gluing specimen was prepared by hot pressing. The present invention prepares a wood gluing specimen (overlap area 25 mm*25 mm) by overlapping, and coats the adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0056] Embodiment 4:
[0057] Step 1: Weigh an appropriate amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH to 9-10, and prepare a 10% PEI aqueous solution;
[0058] Step 2: Weigh an appropriate amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution with a concentration of 10%;
[0059] Step 3: Mix the PEI aqueous solution and the phytic acid aqueous solution in different ratios of 1:1, and continue to slowly stir for 4 hours to obtain a brown viscous substance that is deposited at the bottom of the cup, which is the desired PEI-phytic acid polymer adhesive.
[0060] Step 4: Weigh a certain amount of the above PEI-phytic acid polymer adhesive and add it to a 1% boric acid solution, and stir for 15 minutes to obtain a boric acid cross-linked PEI-phytic acid polymer adhesive.
[0061] Step 5: At a hot pressing temperature of 120°C, a hot pressing pressure of 1.5 MPa, a hot pressing time of 8 minutes, and a single-sided glue amount of 120 g / m 2 Under the condition of , a 2-layer (6 mm thick) gluing specimen was prepared by hot pressing. The present invention prepares a wood gluing specimen (overlap area 25 mm*25 mm) by overlapping, and coats the adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0062] Embodiment five:
[0063] Step 1: Weigh an appropriate amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH to 9-10, and prepare a 10% PEI aqueous solution;
[0064] Step 2: Weigh an appropriate amount of phytic acid stock solution, dissolve it in water, stir evenly, and prepare a phytic acid aqueous solution with a concentration of 10%;
[0065] Step 3: Mix the PEI aqueous solution and the phytic acid aqueous solution in different ratios of 1:1, and continue to slowly stir for 4 hours to obtain a brown viscous substance that is deposited at the bottom of the cup, which is the desired PEI-phytic acid polymer adhesive.
[0066] Step 4: Weigh a certain amount of the above PEI-phytic acid polymer adhesive and add it to a 2% calcium chloride solution, and stir for 15 minutes to obtain a calcium ion cross-linked PEI-phytic acid polymer adhesive.
[0067] Step 5: At a hot pressing temperature of 120°C, a hot pressing pressure of 1.5 MPa, a hot pressing time of 8 minutes, and a single-sided glue amount of 120 g / m 2Under the condition of , a 2-layer (6 mm thick) gluing specimen was prepared by hot pressing. The present invention prepares a wood gluing specimen (overlap area 25 mm*25 mm) by overlapping, and coats the adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0068] Comparative Example:
[0069] Add 50 parts of urea-formaldehyde resin powder into 50 parts of water and continue to stir slowly until the urea-formaldehyde resin is completely dissolved and evenly dispersed to obtain the prepared adhesive.
[0070] Furthermore, the adhesives prepared in the above examples and comparative examples were subjected to the following hot pressing process: hot pressing temperature 120°C, hot pressing pressure 1.5 MPa, hot pressing time 8 min, adhesive application amount 100 g / m 2 , hot pressing is used to prepare a 2-layer (6 mm thick) glued specimen. The present invention prepares a wood glued specimen (overlap area 25 mm*25 mm) by overlapping, and applies an adhesive on the surface of the wood specimen to measure its flame retardant effect.
[0071] Performance Testing
[0072] The dry and wet shear strengths of the overlapped specimens of the embodiment and the control example were measured using a universal testing machine. The oxygen index of the modified wood specimens was measured with reference to GB / T2406-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method". The specific test results are shown in Table 1.
[0073] Example Dry shear strength (MPa) Wet shear strength (MPa) Wood breakage rate (%) Oxygen index (%) Example 1 3.87 0.80 80 45 Example 2 4.16 1.07 85 50 Example 3 5.11 1.62 93 55 Example 4 6.12 2.55 100 61 Example 5 6.33 2.81 100 66 Comparative Example 5.89 2.16 90 26
[0074] Table 1 Bonding strength and flame retardant properties of specimens of different embodiments and reference examples
[0075] It can be seen from the analysis of the test results in Table 1 that the adhesives prepared by the present invention (Examples 1-5) all have good mechanical properties and flame retardant properties. When the concentration of PEI and phytic acid reaches 10% (Example 3), the dry strength is comparable to the bonding strength of the specimens bonded by the traditional urea-formaldehyde resin (comparative example), but the wet strength is relatively low. When the PEI-phytic acid adhesive is cross-linked and modified on this basis (Examples 4 and 5), the dry and wet shear strengths of the prepared specimens are significantly improved, and even superior to the bonding strength of the traditional urea-formaldehyde resin bonded specimens, indicating that the cross-linking modification of boric acid and metal ions can effectively improve the water resistance of the adhesive. In addition, the adhesive prepared with PEI and phytic acid as raw materials is applied on the surface of wood, which can give the wood an excellent flame retardant effect, and the oxygen index is more than twice that of the urea-formaldehyde resin after coating and modification, indicating that the PEI-phytic acid system adhesive has excellent flame retardant properties, and the cross-linking modification of boric acid and metal examples can further enhance the flame retardant effect. Therefore, the PEI-phytic acid adhesive provided by the present invention can not only impart good bonding properties to the artificial board during the preparation process, but also impart excellent flame retardant properties to the artificial board. Moreover, the adhesive of this system is non-toxic, environmentally friendly, and has a simple preparation method. It can replace the traditional urea-formaldehyde resin adhesive in the artificial board industry, solve the formaldehyde pollution problem existing in the preparation of artificial boards by traditional adhesives and the deficiency of the artificial boards themselves being easily flammable, increase the added value and application fields of artificial boards, and further promote the green and sustainable development of the artificial board industry, and has good promotion value.
[0076] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. In all examples shown and described here, unless otherwise specified, any specific value should be interpreted as merely exemplary, rather than as restriction, and therefore, other examples of exemplary embodiments may have different values.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a formaldehyde-free flame-retardant adhesive, characterized in that: The following steps are involved: S1: Weigh a certain amount of high molecular weight polymer polyethyleneimine (PEI), dissolve it in water, stir evenly, adjust the pH value, and prepare a PEI aqueous solution; S2: Weigh a certain amount of phytic acid stock solution, dissolve it in water, and stir evenly to prepare a phytic acid aqueous solution; S3: Mix the PEI aqueous solution and the phytic acid aqueous solution according to a certain ratio, and slowly stir for several hours to obtain a brown viscous substance which is deposited at the bottom of the cup, thereby obtaining a PEI-phytic acid polymer adhesive; S4: adding a cross-linking agent to the PEI-phytic acid polymer adhesive and stirring the mixture evenly to obtain a cross-linked PEI-phytic acid polymer adhesive.
2. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 1, characterized in that: In step S1, the pH is between 9 and 10, the concentration of the prepared PEI aqueous solution is between 2.5% and 10%, and the molecular weight of polyethyleneimine is between 7,000 and 100,000.
3. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 1, characterized in that: In step S2, the concentration of the prepared phytic acid aqueous solution is 2.5%-10%.
4. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 1, characterized in that: In step S3, the mass ratio of the PEI aqueous solution to the phytic acid aqueous solution is 0.25-4.
5. The method for preparing a formaldehyde-free flame-retardant adhesive according to claim 1, characterized in that: In step S4, the cross-linking agent includes boric acid and a metal salt.
6. A formaldehyde-free flame-retardant adhesive, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the formaldehyde-free flame-retardant adhesive according to claim 6 in artificial boards.
8. The use of the formaldehyde-free flame-retardant adhesive in artificial boards as claimed in claim 7, characterized in that: When preparing wood plywood, apply formaldehyde-free flame retardant adhesive at a single-sided application rate of 80-150g / m 2 Apply it to the plate, and then bond it to another plate, and hot press it for 5-15 minutes at a hot pressing temperature of 120-220℃ and a hot pressing pressure of 1-3MPa.
9. The use of the formaldehyde-free flame-retardant adhesive in artificial boards according to claim 7, characterized in that: When preparing fiberboard or particleboard, the formaldehyde-free flame-retardant adhesive is sprayed onto the surface of the fiber or particle board, and hot pressing is performed for 5-15 minutes at a hot pressing temperature of 160-220° C. and a hot pressing pressure of 1-3 MPa.